2021
DOI: 10.3390/jcm10215118
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum High-Density Lipoprotein Cholesterol with High Blood Pressures at Checkup: Results of Kanagawa Investigation of Total Checkup Data from the National Database-9 (KITCHEN-9)

Abstract: Background: although high-density lipoprotein has cardioprotective effects, the association between serum high-density lipoprotein cholesterol (HDL-C) and hypertension is poorly understood. Therefore, we investigated whether high and low concentrations of HDL-C are associated with high blood pressure (HBP) using a large healthcare dataset. Methods: in a community-based cross-sectional study of 1,493,152 Japanese people (830,669 men and 662,483 women) aged 40–74 years who underwent a health checkup, blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The main analysis is as follows: (1) Males and overweight/obese people generally have higher ALT levels ( 45 , 46 ) and lower HDL-C levels than females and non-obese people ( 47 50 ); from a numerical analysis, higher ALT or lower HDL-C means that the ALT/HDL-C ratio will increase; Judging from the results, an elevated ALT/HDL-C ratio corresponded to a heightened risk of diabetes in males and overweight/obese people. (2) From the longitudinal relationship between ALT, HDL-C and age, ALT usually decreases gradually with age ( 51 , 52 ), while HDL-C usually changes less ( 48 , 53 , 54 ); these characteristics will further lead to a reduction in ALT/HDL-C ratio values, thereby reducing the risk of diabetes related to ALT/HDL-C ratio in people over 60 years old. In addition, it should be noted that older people generally have larger HDL particle size, a phenotype that is closely associated with a lower risk of diabetes ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main analysis is as follows: (1) Males and overweight/obese people generally have higher ALT levels ( 45 , 46 ) and lower HDL-C levels than females and non-obese people ( 47 50 ); from a numerical analysis, higher ALT or lower HDL-C means that the ALT/HDL-C ratio will increase; Judging from the results, an elevated ALT/HDL-C ratio corresponded to a heightened risk of diabetes in males and overweight/obese people. (2) From the longitudinal relationship between ALT, HDL-C and age, ALT usually decreases gradually with age ( 51 , 52 ), while HDL-C usually changes less ( 48 , 53 , 54 ); these characteristics will further lead to a reduction in ALT/HDL-C ratio values, thereby reducing the risk of diabetes related to ALT/HDL-C ratio in people over 60 years old. In addition, it should be noted that older people generally have larger HDL particle size, a phenotype that is closely associated with a lower risk of diabetes ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia, either an increase in LDL-C or a decrease in HDL-C, also plays an important role in the development of CVD. Meanwhile, the biological interrelation between hypertension and LDL-C [ 13 , 68 ] or HDL-C [ 12 , 69 , 70 ] has been documented. The structural and functional change in LDL-C and HDL-C, inflammation, and oxidative stress may be associated with vascular atherosclerotic processes, and lead to elevation of blood pressure [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between HDL-C concentration categories and blood pressure are U- or J-shaped [ 69 , 70 , 72 , 73 , 74 ]. In the Kanagawa Investigation of Total Checkup Data from the National Database-9 study, Nakajima et al [ 70 ] found inverted J-shaped relationships between HDL-C and odds ratios for hypertension (≥140/90 mmHg) using the logistic regression analysis method, and both low and extremely high HDL-C concentrations are associated with high blood pressure within both sexes. In the South-West Seoul (SWS) Study, the elderly population with prehypertension combined with low HDL-C showed a twofold higher risk of all-cause mortality (HR: 2.01; 95% CI: 1.11–3.64) [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, we have demonstrated the association of extremely high HDL-C, mostly defined as > 100 mg/dL, with diabetes [17], high blood pressure [18], and hypertensive retinopathy [31]. All of these are well-known risk factors for the incidence of kidney disease and proteinuria [1,2,4].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, we conducted large community-based studies [17,18] showing that very or extremely high HDL-C levels, such as levels over 100 mg/dL or below 50 mg/ dL, may be associated with diabetes and hypertension. These two diseases can impair kidney function over the time and eventually elicit proteinuria, mostly involving albuminuria [1,4].…”
Section: Introductionmentioning
confidence: 99%